Beneficial Effect of Flavone Derivatives on Aβ-Induced Memory Deficit Is Mediated by Peroxisome Proliferator-Activated Receptor γ Coactivator 1α: A Comparative Study. (May 2015) - Arsalandeh, Farshad; Ahmadian, Shahin; Foolad, Forough; Khodagholi, Fariba; Farimani, Mahdi M.; Shaerzadeh, Fatemeh
In the present study, the neuroprotective effect of 5-hydroxy-6, 7, 4′-trimethoxyflavone (flavone 1), a natural flavone, was investigated in comparison with another flavone, 5, 7, 4′-trihydroxyflavone (flavone 2) on the hippocampus of amyloid beta (Aβ)-injected rats. Rats were treated with the 2 flavones (1 mg/kg/d) for 1 week before Aβ injection. Seven days after Aβ administration, memory function of rats was assessed in a passive avoidance test (PAT). Changes in the levels of mitochondrial transcription factor A (TFAM), peroxisome proliferator-activated receptor γ coactivator 1 α (PGC-1α), phospho-adenosine monophosphate (AMP)-activated protein kinase (pAMPK), AMPK, phospho-cAMP-responsive element-binding protein (CREB), CREB, and nuclear respiratory factor 1 (NRF-1) proteins were determined by Western blot analysis. Our results showed an improvement in memory in rats pretreated with flavonoids. At the molecular level, phosphorylation of CREB, known as the master modulator of memory processes, increased. On the other hand, the level of mitochondrial biogenesis factors, PGC-1α and its downstream molecules NRF-1 and TFAM significantly increased by dietary administration of 2 flavones. In addition, flavone 1 and flavone 2 prevented mitochondrial swelling and mitochondrial membrane potential reduction. Our results provided evidence that flavone 1 is more effective than flavone 2 presumably due to its O-methylated groups. In conclusion, it seems that in addition to classical antioxidant effect, flavones exert part of their protective effects through mitochondrial biogenesis.